1998
DOI: 10.1002/(sici)1097-0185(199807)251:3<277::aid-ar1>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial connexin expression in the mare and pig: Evidence for the suppression of cell-cell communication in uterine luminal epithelium

Abstract: This investigation examines the relationship between implantation strategy and gap junction protein expression in uterine endometrium. The pattern of gap junction and connexin protein expression was analyzed in porcine and equine endometrium from cycling and pregnant animals using electron microscopy and immunocytochemistry. Functional analysis of cellcell communication was also monitored by laser cytometry in primary cultures of endometrial epithelial cells. Gap junctions were detected in endometrial stroma o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 21 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Isolation and culture of equine endometrial epithelial and/or stromal cells has previously been described only by a handful of authors (Watson et al 1992, Brady et al 1992, 1993, Burghardt et al 1995, Day et al 1998, Buschatz 2007. The morphology of EEC and ESC cultured in this study reveal matchable results compared to the findings in other species (women and animals) (Satyaswaroop et al 1979, Ricketts et al 1983, Zhang et al 1991) and the mare (Watson et al 1992, Buschatz 2007 without the prejudice of the usage of a serum-reduced culture medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation and culture of equine endometrial epithelial and/or stromal cells has previously been described only by a handful of authors (Watson et al 1992, Brady et al 1992, 1993, Burghardt et al 1995, Day et al 1998, Buschatz 2007. The morphology of EEC and ESC cultured in this study reveal matchable results compared to the findings in other species (women and animals) (Satyaswaroop et al 1979, Ricketts et al 1983, Zhang et al 1991) and the mare (Watson et al 1992, Buschatz 2007 without the prejudice of the usage of a serum-reduced culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…However, little was done to isolate and culture equine epithelial glandular cells and stromal cells (Watson et al 1992, Brady et al 1992, 1993, Day et al 1998, Buschatz 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Schlüsselwörter: Immunhistologie, Zellkultur, Endometrium, Epithelzellen, Pferd (1992) and Buschatz (2007). Brady et al (1992Brady et al ( , 1993, Burghardt et al (1995) and Day et al (1998) cultivated only equine EEC. All of these studies concerning the EEC generally describe primary cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Retinoic acid (RA) and other retinoids have been shown to upregulate GJIC and Cx43 expression levels in a variety of cell types through both transcriptional and translational mechanisms of action (Stahl and Sies, 1998; Carystinos et al, 2001). However, only a few studies describe the effects of RA on the female reproductive system (Day et al, 1998). Our previous work suggested that RA‐mediated dephosphorylation of Cx43 may play a role in the ability of this retinoid to increase GJIC in human ESCs (Tanmahasamut and Sidell, 2005).…”
mentioning
confidence: 99%